Independent mechanisms target SMCHD1 to trimethylated histone H3 lysine 9-modified chromatin and the inactive X chromosome - Brideau, N; Coker, H; Gendrel, A; Siebert, C; Bezstarosti, K; Demmers, J; Poot, R; Nesterova, T; Brockdorff, N (American Society for Microbiology, 2015)
The chromosomal protein SMCHD1 plays an important role in epigenetic silencing at diverse loci, including the inactive X chromosome, imprinted genes, and the Facioscapulohumeral muscular dystrophy locus. Although homology with canonical SMC family proteins suggests a role in chromosome organization, the mechanisms underlying SMCHD1 function and target site selection remain poorly understood. Here we show that SMCHD1 forms an active GHKL-ATPase homodimer, contrasting with canonical SMC complexes which exist as tripartite ring structures. Electron microscopy analysis demonstrates that SMCHD1 homodimers structurally resemble prokaryotic condensins. We further show that the principal mechanism for chromatin loading of SMCHD1 involves LRIF1-mediated interaction with HP1γ at H3K9me3-modified chromatin sites on the chromosome arms. A parallel pathway accounts for chromatin loading at a minority of sites, notably the inactive X chromosome. Together our results provide key insights into SMCHD1 function and target site selection.